Harnessing the Noncovalent Interactions of DNA Backbone with 2D Silicate Nanodisks To Fabricate Injectable Therapeutic Hydrogels - Basu, Sayantani (ACS Nano, 2018)
Injectable hydrogels present several advantages over prefabricated scaffolds including ease of delivery, shear-thinning property, and broad applicability in the fields of drug delivery and tissue engineering. Here, we report an approach to develop injectable hydrogels with sustained drug release properties, exploiting the chemical nature of the DNA backbone and silicate nanodisks. A two-step gelation method is implemented for generating a combination of noncovalent network points, leading to a physically cross-linked hydrogel. The first step initiates the development of an interconnected structure by utilizing DNA denaturation and rehybridization mechanism to form hydrogen bonds between complementary base pairs of neighboring DNA strands. The anisotropic charge distribution of two-dimensional silicate nanodisks (nSi) makes them an active center in the second step of the gelation process. Silicate nanodisks create additional network points via attractive electrostatic interactions with the DNA backbone, thereby enhancing the mechanical resilience of the formulated hydrogel. The thermally stable hydrogels displayed an increase in elasticity and yield stress as a function of nSi concentration. They were able to form self-supporting structures post injection due to their rapid recovery after removal of cyclic stress. Moreover, the presence of nanosilicate was shown to modulate the release of a model osteogenic drug dexamethasone (Dex). The bioactivity of released Dex was confirmed from in vitro osteogenic differentiation of human adipose stem cells and in vivo bone formation in a rat cranial bone defect model. Overall, our DNA-based nanocomposite hydrogel obtained from a combination of noncovalent network points can serve as an injectable material for bone regeneration and carrier for sustained release of therapeutics.